Innovative Waves and Firm Organization in International Trade - Pecka, Lukáš; Čermáková, Klára; Kadeřábková, Božena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2021)
This diploma thesis focuses on the strategic behavior of the firm, which is based on the organization of the industry in which the company operates. The sectors are examined according to the number of innovation waves that are spreading through them, and for this reason, the sectors are divided into less innovative and highly innovative. The innovation of the sector is assessed by the intensity of production on the use of capital and skilled labor, which is perceived as a complement to capital. The aim of this work is to describe the difference in strategic behavior of companies under the influence of normal competition against hypercompetition, or also called the Schumpeterian environment, which is characterized by unceasing fluctuations in market indicators and above-average innovation of production compared to the surrounding economy. The driving force behind strategic behavior here are companies operating primarily on the international market, ie multinational corporations. Their decision-making is monitored between 2009 and 2018 from the perspective of the United States manufacturing industry as the home country of multinational corporations. In addition to the deployment of production and management capacities of companies on the international market, decisions on expanding the product range and their regular innovation, including a combination of these strategies, also play a role. The first part summarizes the theoretical knowledge of strategic behavior in the international market from the perspective of industrial organization. The practical part is devoted to the estimation of models that predict the determinants of effective behavior of companies in these sectors. The conclusion of the thesis is the confirmation of the hypothesis that companies operating in more innovative sectors survive in the market thanks to a more significant regular updating of products and expansion of the product portfolio.
The hypothesis that companies from more innovative sectors geographically diversify their production to countries with a comparable supply of capital and skilled labor despite the distance is rejected.
Vedoucí práce: Klára Čermáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses